Brief Report: Lysyl Oxidase Is a Potential Biomarker of Fibrosis in Systemic Sclerosis. Issue 3 (March 2014) - Rimar, Doron; Rosner, Itzhak; Nov, Yuval; Slobodin, Gleb; Rozenbaum, Michael; Halasz, Katy; Haj, Tharwat; Jiries, Nizar; Kaly, Lisa; Boulman, Nina; Daood, Rula; Vadasz, Zahava
<x xml:space="preserve">Abstract</x> Objective Fibrosis is a major cause of morbidity and mortality in systemic sclerosis (SSc). Levels of lysyl oxidase (LOX), an extracellular enzyme that stabilizes collagen fibrils, have been found to be elevated in the skin of SSc patients, but have not been evaluated in the serum or correlated with the clinical parameters. We undertook this study to evaluate serum LOX levels in SSc patients and to correlate these levels with clinical parameters of SSc. Methods SSc patients were evaluated for demographic features, clinical manifestations, routine laboratory tests, serum autoantibodies, serum LOX concentrations, and nailfold capillaroscopy patterns. They underwent pulmonary function testing, echocardiography, and high‐resolution computed tomography scans of the lung, assessment of skin fibrosis by the modified Rodnan skin thickness score (MRSS), and assessment of disease severity and activity by the Medsger severity scale and the Valentini activity index. Results Twenty‐six SSc patients were evaluated and compared with 25 healthy controls and with 9 disease control patients with primary myelofibrosis. Almost 62% of the SSc patients (16 of 26) had limited cutaneous SSc (lcSSc), while 38% had diffuse cutaneous SSc (dcSSc) (10 of 26); 31% of the patients (8 of 26) had lung involvement. The LOX concentration in SSc patients was higher than that in healthy controls and similar to that in disease controls (P < 0.0001), and it was significantly higher in patients with dcSSc than in those with lcSSc (P = 0.006). The LOX concentration correlated with the MRSS in patients without lung fibrosis. Conclusion This study is the first to demonstrate high serum LOX levels in SSc patients that correlate specifically with skin fibrosis. These correlations suggest that LOX levels may serve as a novel biomarker of fibrosis. Future studies are warranted to determine whether LOX is a potential therapeutic target in SSc.